2012
DOI: 10.1103/physrevlett.109.013901
|View full text |Cite
|
Sign up to set email alerts
|

Weak Measurements of Light Chirality with a Plasmonic Slit

Abstract: We examine, both experimentally and theoretically, an interaction of tightly focused polarized light with a slit on a metal surface supporting plasmon-polariton modes. Remarkably, this simple system can be highly sensitive to the polarization of the incident light and offers a perfect quantum weak measurement tool with a built-in postselection in the plasmon-polariton mode. We observe the plasmonic spin Hall effect in both coordinate and momentum spaces which is interpreted as weak measurements of the helicity… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
176
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(181 citation statements)
references
References 38 publications
2
176
0
Order By: Relevance
“…This induces a rotation of the fields in the propagation (x,z) plane (see Fig. 2a,d), and generates the spin s y / Im E Ã z E x þ H Ã z H x À Á independently of s. Recently, we described such spin for surface plasmon-polaritons 42 , and it was shown that the imaginary longitudinal field component plays an important role in optical coupling processes 44,45 . The second feature is the inhomogeneous intensity wpexp( À 2kx).…”
Section: Resultsmentioning
confidence: 99%
“…This induces a rotation of the fields in the propagation (x,z) plane (see Fig. 2a,d), and generates the spin s y / Im E Ã z E x þ H Ã z H x À Á independently of s. Recently, we described such spin for surface plasmon-polaritons 42 , and it was shown that the imaginary longitudinal field component plays an important role in optical coupling processes 44,45 . The second feature is the inhomogeneous intensity wpexp( À 2kx).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, we have shown that the new effect of near-field interference enables the broadband mapping of light in space, depending on its polarization handedness. This mapping is similar to the spin Hall effect, which has recently been considered also in optical domain for new quantum optical applications 7,8,10,11 employing the structured interfaces to break the inversion symmetry. In our realization, this effect is observed due to the inversion symmetry broken by the radiating dipole.…”
Section: Discussionmentioning
confidence: 85%
“…The approach based on discrete nanoresonators and their arrangements in various kinds of metamaterials has already resulted in many applications, such as cloaking 3 and perfect lensing 4 , as well as spontaneous emission and nonlinearity engineering 5 . The direction of light propagation can also be controlled by the polarization degree of freedom [6][7][8][9][10][11][12] . In particular, when circularly polarized light interacts with specifically designed nanostructured metasurfaces that break spatial inversion symmetry, photons of different polarizations (optical spin) may take different trajectories, in close analogy to the spin Hall effect for electrons [7][8][9][10][11] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, such a spin-orbit coupling can also occur even for a scatterer with other shapes in scattering the incident light to surface plasmon. Figure 8A shows an example of a single slit illuminated by a tightly focused linearly or elliptically polarized light beam [96]. The shift in either the focal point or the direction of the generated surface waves is measured using a "weak measurement" approach.…”
Section: Surface Plasmon Generation With Geometric-phase Metasurfacesmentioning
confidence: 99%